The bar code rebellion - Weyn, Suzanne (New York : Scholastic, 2012)
Kayla's life and her freedom are threatened when she refuses to get the bar code tattoo.
Young Adult
Young Adult.
880
Keywords: Identity (Psychology) -- Juvenile fiction; Bar coding -- Juvenile fiction; Tattooing -- Juvenile fiction; Identity -- Fiction; Bar coding -- Fiction; Tattooing -- Fiction; Science fiction; Identity (Psychology) -- Fiction; Bar coding -- Fiction; Tattooing -- Fiction; Science fiction; Science fiction